Growth Rates and Correlations between some Growth Parameters of Sunflowers (Helianthus annuus L.) Irradiated Plants - Dafalla, Mashaeir F.; Kehail, Mutaman A.; Abashar, Abasher A.; Abdelrahim, Yassir M. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
Sunshine is a type of radiation that is needed for photosynthesis and normal plant growth,so, no all radiation is bad. This study aimed to evaluate the growth rates and correlationbetween them in sunflower (Helianthus annuus L.) irradiated with X-ray, Gamma-ray,and UV-light. The experiment was conducted in 2020, in the experimental farm, Facultyof Agriculture, University of Gezira, Sudan. A well-known variety of sunflower seedswere brought from Agricultural Research Corporation, Wad Medani, Gezira State, Sudan.The sunflower seeds were submitted separately to two treatments of X-ray (33.4 (LX)and 200.2 sec (HX), gamma-ray (200 (LG) and 800 cGy (HG)) and UV-light (for 30 sec.(UV)). In addition to control, all irradiated sunflower seeds were grown under the sameenvironmental conditions. The growth parameters (plant weight, height, diameter, No. ofleaves, tall, and width of leaves) were recorded every 10 days till 60 days. The results ofthis study revealed that LX sunflower plants have a daily increase in net weight of 0.24 g;0.90 cm in stem tall; 0.03 cm in stem diameter; 0.12 cm in leaves tall; 0.06 cm in leaveswidth and 0.36 in leaves number, compared to 0.22 g in net weight; 1.10 cm in stem tall;0.03 cm in stem diameter; 0.17 cm in leaves tall; 0.13 cm in leaves width and 0.36 inleaves number in C, white it was 0.09 g in net weight; 0.68 cm in stem tall; 0.01 cm instem diameter; 0.04 cm in leaves tall; 0.01 cm in leaves width and 0.27 in leaves numberin HG, which are relatively less than that of LX, HX and LG. Most of the growthparameters correlated to each other by a positive factor of more than (0.95). Furtherstudies should be conducted to evaluate the nutritional contents and human allergicability.